Efeito das condições climáticas do semiárido sobre o comportamento fisiológico de caprinos mestiços f1 Saanen x Boer - Silva, Carlos Magno Bezerra de Azevedo; de Souza, Bonifácio Benício; Brandão, Patrícia de Araújo; Marinho, Paulo Vinícius Tertuliano [UNESP]; Benício, Talícia Maria Alves (My University, 2011)
This research aimed at evaluating the effect of the semiarid climatic conditions on the physiological behavior of F1 Saanen x Boer crossbred goats, created at an intensive system. The experiment was carried out in the Health and Rural Technology Center, in the Federal University of Campina Grande, in the town of Patos, Paraiba. Twenty-four animals were used, with ages varying between three and four months, being 12 females and 12 males, weaned and prevented against worms, receiving ad libitum water and controlled concentrate and roughage. The environmental variables were checked inside and outside the experiment place, as well as the physiological variables of all animals. Except for the humid bulb temperature, the variance analysis revealed shift effect (P<0.05) for all environmental variables. There was merely shift effect (P<0.05) for Cardiac Frequency and Rectal Temperature, and the averages of both, in the afternoon, overcame those observed in the morning. The obtained results based on the studied physiological and environmental variables conclude that crossbred goats, resulting of Boer (paternal) and Saanen (maternal), present a good resistance to heat, permitting their indication for the meat production in confinement on semiarid conditions.
Effect of the semiarid climatic conditions on the physiological behavior of Saanen x Boer crossbred goats
Keywords: Adaptation; Environmental variables; Intensive system; Physiological variables